The Effect of Problem Based Learning (PBL) with Scaffolding on High School Students' Creative Thinking Skills - Hasanah, Rahmah Nurul Aina; Hamdiyati, Yanti; Mimin Nurjhani K. (Bioeduca : Journal of Biology Education, 2025)
This study was conducted to determine whether there is a difference in students' creative thinking skills before and after problem-based learning with scaffolding . The instruments used in this study were a creative thinking skills test instrument and a non-test instrument consisting of an observation sheet and a student response questionnaire. The results of statistical tests showed a significant difference in creative thinking skills after problem-based learning with scaffolding . This is also indicated by the increase in test results in the moderate category in the control class by 53% and in the experimental class by 72% in the same category, resulting in a gain value of 0.33 (moderate). In addition, there was a positive response to problem-based learning with scaffolding  as seen in the average percentage of agreement in student responses, namely 84%, which is included in the very good category